Types of 23S Ribosomal RNA Point Mutations and Therapeutic Outcomes for Helicobacter pylori - Sang Yoon Kim; Jae Myung Park; Chul-Hyun Lim; Hye Ah Lee; Ga-Yeong Shin; Younghee Choe; Yu Kyung Cho; Myung-Gyu Choi (Gut and Liver, 2021)
Background/Aims: Point mutations in the 23S ribosomal RNA gene have been associated with Helicobacter pylori clarithromycin resistance. This study aimed to detect the prevalence of these point mutations and to investigate the role of different point mutations in the success of eradication therapy. Methods: We retrospectively investigated a total of 464 consecutive patients who underwent an endoscopic examination and dual-priming oligonucleotide-based multiplex polymerase chain reaction for H. pylori between June 2014 and October 2019. For 289 patients with negative point mutations, standard triple therapy was used in 287 patients, and the bismuth-quadruple regimen was used in two patients. For 175 patients with positive point mutations (A2142G, A2143G, and both mutations), standard triple and bismuth-quadruple therapies were used in 37 patients and 138 patients, respectively. Results: The eradication rates of standard triple and bismuth-quadruple therapies showed no significant difference in mutation-negative patients or those with the A2142G point mutation. However, the eradication rate with bismuth-quadruple therapy was significantly higher than that with standard triple therapy in the group with the A2143G mutation or with the double mutation. The eradication rates for standard triple and bismuth-quadruple therapies, respectively, were 25.8% and 92.1% in the per-protocol group (p<0.001) and 24.2% and 85.2% in the intention-totreat analysis (p<0.001). Conclusions: The A2143G point mutation is the most prevalent cause of clarithromycin resistance. Bismuth-quadruple therapy is superior to standard triple therapy in patients with the A2143G or double point mutation.